(3TQM Ydi GdWgGQIs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdWgGQI, GdWgGQI dZI gj GdfRGgI hGdfXGaI hgeG aj cd TjA jMSf hYfO GdTQY Ch GdeTQYI ZSd HGdeGA Ch eSM HGdJQGH eJYdb HGdHOf Ydi hLg dg UdGMjI GdJCKjQ aj GdYHGOIs
(3BNQgG (B:s
(3BNQgG(B: (3hQHeG jfGbT HCfg djS aj ebGe HjGf GWdGb GdWghQ Ydi GdhVhA Hbhd (B.. (3ceG dG jNais
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis